Estonia – Highly Unequal but Classless? - Helemäe, Jelena; Saar, Ellu (Studies of Transition States and Societies, 2012)
In this short essay, we try to assess the utility of class analyses for understanding the contemporary Estonian society. Erik Wright (2009) identiﬁ es three strands of class analysis: a stratiﬁ cation approach, a Weberian approach and a Marxist approach. We address the following questions: Which kind of class analysis is most present in Estonia today? Which is most needed? The main conclusion is that due to this marginalisation of class discourse, as well as the power of national/ethnic discourse and transitional culture, those most economically vulnerable were deprived of the cultural and discursive resources to resist the most the extreme market-oriented policies. The conditions for structuration of class relations were created, while the class and inequality discourse was marginalised.